2021
DOI: 10.1002/aah.10116
|View full text |Cite
|
Sign up to set email alerts
|

Reference Intervals for Blood Analytes of Adult Aquarium‐Housed Russian Sturgeon Acipenser gueldenstaedtii

Abstract: Russian Sturgeon Acipenser gueldenstaedtii are an important, critically endangered, roe‐producing species. Despite a wealth of knowledge pertaining to other members of family Acipenseridae, there is very limited published information regarding baseline blood analytes in Russian Sturgeon. The objectives of this study were (1) to establish reference intervals for a suite of hematological and biochemical data and (2) to compare plasma chemistry data to two point‐of‐care (POC) cartridges, tested on the VetScan iST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
2
4
0
1
Order By: Relevance
“…No clear trends in PCV were appreciable by site or year ( Table 2 ); however, female lake sturgeon had lower mean PCVs in both year one and two at the Black River site when compared to males ( Table 2 ). PCV measurements were comparable to reference intervals established by DiVincenti et al (2013) and Cassle et al (2013) [ 48 , 49 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…No clear trends in PCV were appreciable by site or year ( Table 2 ); however, female lake sturgeon had lower mean PCVs in both year one and two at the Black River site when compared to males ( Table 2 ). PCV measurements were comparable to reference intervals established by DiVincenti et al (2013) and Cassle et al (2013) [ 48 , 49 ].…”
Section: Resultssupporting
confidence: 87%
“…There is little published information regarding the relationships between hematologic parameters, such as packed cell volume, and alloherpesvirus infection. Overall, this study found no substantial differences in PCV between male and female fish from any site in any year, and all PCV averages fell within published sturgeon ( A. fulvescens and A. gueldenstaiedtii ) reference intervals (17–38% and 16–34%) [ 48 , 49 ].…”
Section: Discussionsupporting
confidence: 52%
“…This study establishes blood biochemical RIs for Chinese sturgeon and is an essential first step in the application of these parameters to Aramli et al, 2013;Asadi et al, 2006;Cassle et al, 2021;Di Marco et al, 2011;DiVincenti Jr. et al, 2013;Matsche et al, 2013;Matsche et al, 2014;Shahsavani et al, 2010;Shi et al, 2006). Compared to other sturgeons, there are fewer studies on Chinese sturgeon that can be directly compared to our study.…”
Section: Ris For Serum and Mucous Biochemical Parametersmentioning
confidence: 94%
“…Ancak balıklarda referans değerlerini belirlemek son derece zordur ve çoğu kan parametresinin normal aralıkları, balığın iç ortamının poikilotermiye bağlı kararsızlığı ve dış etkenlere karşı yüksek duyarlılığı nedeniyle çok geniştir (Luskova, 1997;Witeska, 2015). Bu nedenle yapılacak çalışmalarda referans aralıklarını cinsiyet, yaş, cinsi olgunluk durumu gibi biyotik ve abiyotik faktörlere göre belirlemek bir tanı aracı olarak hematolojik ve biyokimyasal analizlerin doğruluğunu ve kullanışlılığını artırır (Cassle, 2021). Bununla birlikte, numune alım tekniklerinin ve kan analizlerinin standardize edilmesi yaklaşımı da hematolojik ve biyokimyasal analizlerin doğruluğunu destekleyici nitelikte olacaktır (Fazio, 2019).…”
Section: Bulgular Ve Tartişmaunclassified